Analysis of Outdoor to Indoor Penetration Loss at 28 and 38 GHz Channels - Adaika, Abdelhafidh; Mebarki, Abdelhafidh; Hermes, Mohammed (Echahid Hama Lakhdar University of Eloued, 2023)
"Abstract: The fifth generation (5G) of cellular network, known as 5G, brings significant advancements to mobile cellular communication by operating at millimeter wave frequencies (mmWave). In the realm of mmWave communication, one of the prominent frequency bands in 5G is the 28 GHz band. In this study, we aim to explore the characteristics of the 28 and 38 GHz bands within a Line of Sight (LOS) environment. LOS is crucial for various radio transmissions as it represents a direct path between the radio transmitter and receiver. Our research primarily focuses on the Urban microcell scenario in El-Oued, Algeria, specifically investigating the number of antenna elements required for optimal performance. Furthermore, we analysed the radio propagation performance by examining time delays (Root Mean Square – RMS), signal attenuation, received power, angle of departure (AoD), and angle of arrival (AoA) in both azimuth and elevation dimensions." " ملخص: يحقق الجيل الخامس (5G) من الشبكة الخلوية، المعروف باسم 5G، تطورات كبيرة في الاتصالات الخلوية المتنقلة من خلال التشغيل عند ترددات الموجات المليمترية (mmWave). في عالم اتصالات mmWave، أحد نطاقات التردد البارزة في 5G هو النطاق 28 جيجاهرتز. في هذه الدراسة، نهدف إلى استكشاف خصائص النطاقين 28 و38 جيجاهرتز ضمن بيئة خط البصر (LOS). يعد LOS أمرًا بالغ الأهمية لعمليات الإرسال الراديوية المختلفة لأنه يمثل مسارًا مباشرًا بين جهاز الإرسال والاستقبال الراديوي. يركز بحثنا بشكل أساسي على سيناريو الخلايا الصغيرة الحضرية في الواد بالجزائر، وتحديداً في التحقق من عدد عناصر الهوائي المطلوبة لتحقيق الأداء الأمثل. علاوة على ذلك، نقوم بتحليل أداء الانتشار الراديوي من خلال فحص التأخيرات الزمنية (مربع متوسط الجذر - RMS)، وتوهين الإشارة، والقدرة المستقبلة، وزاوية المغادرة (AoD)، وزاوية الوصول (AoA) في كل من أبعاد السمت والارتفاع. "
مذكرة ماستر اتصالات Des thèses télécominication
Keywords: outdoor-to-indoor propagation, mmWave, path loss, MIMO, Channal Modal; انتشار خارجي إلى داخلي، الموجة الميليمترية، خسارة المسير، MIMO، نموذج القناة.